Hydrologic and Geochemical Research at Pinios Hydrologic Observatory: Initial Results. Issue 1 (8th November 2018) - Pisinaras, Vassilios; Panagopoulos, Andreas; Herrmann, Frank; Bogena, Heye R.; Doulgeris, Charalampos; Ilias, Andreas; Tziritis, Evangelos; Wendland, Frank
Abstract : Core Ideas: Modeled ETo gradients present variations as a function of altitude, annual cycle, and total amount. A very good match between different soil moisture monitoring devices has been achieved. Groundwater level monitoring revealed dominant hydrodynamic evolution mechanisms. Hydrochemical monitoring supports groundwater hydrology findings and reveals pollution sources. Monitoring the PHO supports accurate hydrologic modeling and sustainable water use. The Pinios Hydrologic Observatory (PHO) is located in the River Pinios basin, which is one of the most productive basins in Greece. The PHO was established to develop deep knowledge of water balance at the river basin scale and to improve understanding of the major hydrodynamic mechanisms to improve hydrological modeling and ultimately sustainable water resource management. The PHO comprises three meteorological stations, 12 groundwater monitoring sites, and one soil moisture monitoring site, which includes frequency domain reflectometry sensors (SoilNet) and a cosmic‐ray neutron sensor (CRNS) probe. Although the PHO was recently established (at the end of 2015), the preliminary findings from data analysis are promising. Calculated reference evapotranspiration (ETo) gradients demonstrate differences regarding their annual cycle, total amount, and altitude level. Moreover, climate analysis indicates nocturnal mountain‐valley winds. Groundwater level spatial distribution indicates the dominant recharge mechanisms to the alluvial aquifer system. These findings are also supported by the hydrochemical data analysis (electrical conductivity and, secondarily, NO3 distribution). Locally elevated NO3 concentrations are attributed to agricultural activities and call for review of the adopted farming practices. Results from the soil moisture monitoring site indicate a very good match between the CRNS probe and the average SoilNet data. Future perspectives of the PHO include geophysical surveys to accurately delineate the geometry of the groundwater system, the expansion of groundwater and soil moisture observation networks, and the application of the mGROWA hydrologic model to accurately simulate the hydrological processes in the PHO and upscale in the entire River Pinios basin. Finally, in support of the local farmers, we plan to develop and implement a distributed irrigation programming protocol in the entire area of the PHO.